Photo-oxidation of pre-treated palm oil mill Effluent using cylindrical column immobilized photoreactor - Mohammed Haji, Alhaji; Khairuddin, Sanaullah; Shanti Faridah, Salleh; Rubiyah, Baini; Lim, Soh Fong; Andrew Ragai, Henry Rigit; Khairul Anwar, Mohamad Said; Afrasyab, Khan (Elsevier B.V., 2018)
Photooxidative degradation of pre-treated Palm oil mill effluent for removal of chemical oxygen demand, biological oxygen demand and color by UV/TiO2 system has been investigated in a cylindrical glass photoreactor whose outer surface has been coated with titanium dioxide whereas the UV source has been placed inside the glass tube. The removal of these pollutants indicators has been found to follow pseudo-first-order kinetics and hence the electrical energy per order (EEO) figure-of-merit is used to calculate approximately the electrical energy efficiency of the advanced oxidation process system. The higher dissolved oxygen (10 mg/L), lower initial concentration (6 mg/L) and acidic medium (pH = 3) have been found favorable to the photocatalytic degradation of palm oil mill effluent.